2007
DOI: 10.1007/s10654-007-9121-6
|View full text |Cite
|
Sign up to set email alerts
|

Association between tobacco smoke exposure and levels of C-reactive protein in the Oslo II Study

Abstract: It is well known that tobacco smoke exposure is related to the risk of developing cardiovascular diseases and events. One mechanism could be that tobacco smoke acts on the cardiovascular system by altering the autonomic function and/or inducing inflammatory responses. We used data from 3 744 men aged 67-77 years from the city of Oslo that participated in the health screening for the Oslo II Health Study in 2000, to explore associations between C-reactive protein and environmental exposures including exposure t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 41 publications
(33 reference statements)
3
22
0
3
Order By: Relevance
“…In addition, hsCRP is associated with atherosclerotic processes40 and thus may also be directly involved in cardiovascular injury. The high sensitivity of this test, as indicated by significant differences via secondhand smoking exposure and consistent results for different indices of tobacco exposure in ELSA‐Brasil and across other studies,5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 41 highlights hsCRP as a favorable marker for monitoring hazardous health effects of tobacco exposure.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…In addition, hsCRP is associated with atherosclerotic processes40 and thus may also be directly involved in cardiovascular injury. The high sensitivity of this test, as indicated by significant differences via secondhand smoking exposure and consistent results for different indices of tobacco exposure in ELSA‐Brasil and across other studies,5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 41 highlights hsCRP as a favorable marker for monitoring hazardous health effects of tobacco exposure.…”
Section: Discussionsupporting
confidence: 73%
“…These studies have generally shown higher levels of hsCRP among current and former smokers compared with nonsmokers5, 6, 9, 10, 12, 13, 14, 15 and decreased levels after smoking cessation, albeit slower than systolic blood pressure and total cholesterol and LDL‐C 8, 11, 12. Calculating the probability of CAC onset following smoking exposure in the Heinz Nixdorf Recall study also demonstrated that onset of CAC was expedited by 10 years among current smokers and 5 years among former smokers compared with never smokers 16.…”
Section: Discussionmentioning
confidence: 98%
“…A few studies consistently reported that current smokers had a higher CRP level than ex-smokers and/or nonsmokers [12,13,[21][22][23] and several studies found a doseresponse relationship of pack-years of smoking and number of cigarettes smoked daily with elevated CRP levels [12,13,22]. Our study discovered that the number of cigarettes smoked per day was significantly related to elevated serum CRP levels after adjusting for potential confounders.…”
Section: Association Between Cigarette Smoking and Inflammatory Markerssupporting
confidence: 61%
“…Some studies revealed a dose-response relationship between the smoking pack-year and the number of cigarettes smoked daily with elevated CRP levels [15, 16, 30]. Similarly, we found that the number of cigarettes smoked per day was significantly related to elevated serum CRP levels.…”
Section: Discussionsupporting
confidence: 82%
“…Studies on cigarette smoking and CRP in men have consistently shown that current smokers have a higher level of CRP than exsmokers and nonsmokers [15, 16, 30, 31]. Some studies revealed a dose-response relationship between the smoking pack-year and the number of cigarettes smoked daily with elevated CRP levels [15, 16, 30].…”
Section: Discussionmentioning
confidence: 99%